A Comparison of Freezing Injury in Oat and Rye: Two Cereals at the Extremes of Freezing Tolerance. - Webb, M. S. (1994)
A detailed analysis of cold acclimation of a winter rye (Secale cereale L. cv Puma), a winter oat (Avena sativa L. cv Kanota), and a spring oat cultivar (Ogle) revealed that freezing injury of leaves of nonacclimated seedlings occurred at -2[deg]C in both the winter and spring cultivars of oat but did not occur in winter rye leaves until after freezing at -4[deg]C. The maximum freezing tolerance was attained in all cultivars after 4 weeks of cold acclimation, and the temperature at which 50% electrolyte leakage occurred decreased to -8[deg]C for spring oat, -10[deg]C for winter oat, and -21[deg]C for winter rye. In protoplasts isolated from leaves of nonacclimated spring oat, expansion-induced lysis was the predominant form of injury over the range of -2 to -4[deg]C. At temperatures lower than -4[deg]C, loss of osmotic responsiveness, which was associated with the formation of the hexagonal II phase in the plasma membrane and subtending lamellae, was the predominant form of injury. In protoplasts isolated from leaves of cold-acclimated oat, loss of osmotic responsiveness was the predominant form of injury at all injurious temperatures; however, the hexagonal II phase was not observed. Rather, injury was associated with the occurrence of localized deviations of the plasma membrane fracture plane to closely appressed lamellae, which we refer to as the "fracture-jump lesion." Although the freeze-induced lesions in the plasma membrane of protoplasts of spring oat were identical with those reported previously for protoplasts of winter rye, they occurred at significantly higher temperatures that correspond to the lethal freezing temperature.